Ornamen Nusantara Sebagai Sumber Inspirasi Penciptaan Lukisan Pada Kain Sutra - Utomo, M. Indra Bayu; Setem, I Wayan; Yudha, I Made Bendi (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2022)
In writing this final report, the author raised the theme of ornament as a source of inspiration for creating paintings on silk. Silk painting is a type of craft product originating from China and India since the 2nd century AD. Silk painting entered Indonesia about 200 years later because of the trade relations between Indonesia and China and India. Although the art of silk painting has long been known in Indonesia, the art of silk painting is still not developed like other types of craft products that have been widely developed in Indonesia. Because when the influence of silk painting entered Indonesia, Indonesia had already developed the batik industry. The art of silk painting itself is more or less influenced by batik techniques. The author develops archipelago ornaments in the creation of paintings on fabrics, especially silk, the techniques studied are very interesting for the development of painting techniques. Therefore, the author makes 6 beautiful works that have their own ornamental style, besides that the author also develops the creation of archipelago ornaments by creating new ornaments on both denim and silk fabrics with different methods and techniques